Designing hospital services: findings from a prevalence study on clinical and care complexity in the Internal Medicine Units of Bologna’s Local Health Authority - Mazzoli, Sofia; Ricci, Matteo; Golfieri, Chiara; Canto, Federica; Paciotti, Monica; Iannone, Primiamo; Carnuccio, Vincenzo; Lazzari, Claudio; Gori, Davide; Rallo, Flavia (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Hospital services face significant challenges: responding to patients’ increasingly complex care and assistance needs and optimizing the scarce resources available. In this context, the following study aims to map and analyze the clinical and care complexity required by patients admitted to the Internal Medicine Units of the Local Health Authority of Bologna through a variant of the Triage in Corridor tool. Study design. Prevalence Study. Methods. Two measurements were carried out at six Internal Medicine Units of the Ospedale Maggiore (Main Hospital with the role of Hub hospital) and six Internal Medicine Units of six Spoke hospitals of the Local Health Authority of Bologna. The National Early Warning Score and the Assistance Dependency Index scores were measured and then combined in a variant of the Triage in Corridor tool to evaluate the intensity of care required by patients. Results. Data were collected from 342 patients at the first and 319 at the second measurements. In the Hub hospital, 33.1% of patients had low levels of modified Triage in Corridor at first and 29.3% at the second measurements, while in the Spoke hospitals, it was 37.2% and 39.0%, respectively. Intermediate levels included most patients: in the Hub hospital, 49.7% at the first measurement and 47.6% at the second, while in the Spoke, it was 46.1% and 47.1%, respectively. High levels affected 17.2% of patients at the first measurement in the Hub hospital and 23.1% at the second measurement, compared with 16.8% and 14.0% in the Spoke hospitals. Conclusion. The results of this study indicate that almost half of the patients admitted to the Internal Medicine Units included in the study had a modified Triage in Corridor medium level regarding the intensity of care required. Patients with a low level represented approximately one-third of the total, opening the doors to alternative scenarios to the traditional acute hospital where this type of patient can be assisted.